Analysis of Income of Partnered and Non-Partnered Palm Sugar Craftsmen in Pacitan Regency: Analisis Pendapatan Pengrajin Gula Kelapa Bermitra dan Tidak Bermitra di Kabupaten Pacitan - Aziz Al Ghifari; Mubarokah; Risqi Firdaus Setiawan (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
The differences in facilities received by partnered and non-partnered palm sugar craftsmen lead to disparities in their income. This study aims to analyze the income of partnered and non-partnered palm sugar craftsmen affiliated with ISM Manggarsari in Mantren Village, Kebonagung District, Pacitan Regency. The sample consists of 60 palm sugar craftsmen selected through simple random sampling. Primary data were analyzed using income analysis and independent sample t-test with SPSS. The results show that the cash cost-based income of partnered craftsmen is higher (Rp899.049/month) compared to non-partnered craftsmen (Rp682.818/month), driven by better production volume (68.80 kg/month) and selling price (Rp13.500/kg). However, total cash cost-based income indicates losses for both groups (partnered: -Rp462.352; non-partnered: -Rp903.976), primarily due to uncompensated family labor costs. The t-test (Sig. 0.014 < 0.05) confirms a significant difference in income between the two groups. It is recommended that non-partnered craftsmen join partnerships to gain market access and develop derivative products for sustainable profitability.